Ensuring Access to Neurologic Care: Challenges and Opportunities - Hill, Chloé E.; Lin, Chun Chieh; Callaghan, Brian C. (Seminars in Neurology, 2025)
Neurologic disorders are prevalent in the United States, with an estimated 60% of Americans experiencing at least one neurologic condition. This volume of neurologic disease requires commensurate care. In this article, we review access to neurologic care and examine challenges and opportunities across several dimensions of access. Long wait times for neurologists and evidence that neurologists see only a fraction of certain neurologic conditions suggest issues with the availability of care; better triage of neurologists' expertise and employment of neurology advanced practice providers may improve the supply of neurologic care. Accessibility of neurologic care is hindered by regional inequities and urban/rural disparities, which may be attenuated through the use of telemedicine. High out-of-pocket costs and excessive pharmaceutical prices inhibit the affordability of neurologic care; these obstacles may be addressed with more appropriate test utilization and more effective drug price negotiation. Lastly, innovative care models facilitated by recent technological advances have the potential to profoundly expand access to neurologic care.
Keywords: access; neurology; workforce; advanced practice providers; telehealth; telemedicine